Analisis Dampak Pengurangan Pajak Tahunan Kendaraan Listrik Murni dan Insentif Bea Masuk Bahan Baku Kendaraan Listrik bagi Tingkat Penjualan Kendaraan Listrik - Gilbertus Brian; Sudirgo, Tony (CV. Creative Tugu Pena, 2024)
The development of the electric vehicle ecosystem in Indonesia is one of the government's main plans. And its adaptation is encouraged through various policies, including fiscal policies such as the reduction of annual tax on pure electric vehicles (PKB) and the elimination of import duties on raw materials for electric vehicles. This policy has been running for 2-3 years, so its impact can be evaluated to assess its effectiveness in increasing sales of pure electric vehicles in Indonesia. The purpose of this study is to analyze the impact of the annual PKB reduction of pure electric vehicles and import duty incentives on the sales level of electric vehicles in Indonesia during the period 2020-2023. The variables used include the number of electric vehicles sold, annual PKB reduction, and raw material import duty incentives. The results obtained show that the PKB reduction has no significant positive effect on the level of electric vehicle sales. In addition, import duty incentives are positively correlated with sales levels, although they remain statistically insignificant and do not moderate the effect of the PKB reduction. This indicates that although fiscal policy has the potential to support the sales of electric vehicles, its implementation has not been effective in supporting the achievement of the expected target, so it can be concluded that fiscal incentive policies are not sufficient to encourage the growth of the electric vehicle market in Indonesia. In order to increase the adoption of electric vehicles, greater incentives are needed as well as additional policies such as widespread socialization of incentive programs utilizing various media, development of adequate supporting infrastructure, and increasing the amount of investment in the development of technology and the national electric vehicle industry.